Social Inequality Viewed From The Top Of Morro: An Analysis Of Rap Cancao Infantil, By Cesar Mc - Ramalhete, Mariana Passos; Moreira, Tatiana Aparecida (Editora Univ Pontificia Univ Catolica Rio Grande Sul-edipucrs, 2021)
This work analyzes, in the light of the enunciative-discursive perspective language from authors of Bakhtin Circle, the rap Cancao Infantil, written by the capixaba Cesar MC. It starts from the premise that, in an unequal society, the sign is more than a tangle of words: it is ideological, an arena where class struggle develops. Thus, through a qualitative approach of documental procedure, it dis- cusses how this rap, based on the simultaneous allusion to the symbolic and the real, gives visibility to the consequences of social inequality, by addressing part of the problems inherent to the periphery. The article concludes that rap music, in addition to exposing the wounds and contradictions of Brazilian society, in a cyclical and dual positioning, moves away from a marginalized and/or glamorized perspective of poverty, from less superficial and, therefore, less Manichaeans.
Keywords: Active responsive attitude; Cancao Infantil; Dialogism; Plurilingualism; Rap